2023
DOI: 10.7717/peerj.14595
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontitis and COVID-19 infection: a two-sample Mendelian randomization study

Abstract: Background and Objective Epidemiological studies report associations between coronavirus disease 2019 (COVID-19) and periodontitis; however, causality has not been proven. The aim of this study is to assess the associations between COVID-19 susceptibility and periodontitis with two-sample Mendelian randomization (MR) analyses. Methods A two-sample summary MR analysis was performed using data for outcome and exposure from the OpenGWAS databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Wang et al investigated the causal relationship between periodontitis and SARS-CoV-2 infection based on MR (Mendelian Randomization) methods and concluded that there is a causal relationship between periodontitis and SARS-CoV-2 infection. [43] In their study, Meng et al found that periodontitis and GCF (Gingival crevicular uid) IL-1β (Interleukin-1β) levels, which are higher in periodontitis, are causally related to increased susceptibility to SARS-CoV-2 infection [21]. On the other hand, a study by Drozdzik et al showed that there was no causal connection between periodontitis and SARS-CoV-2 cases, but it was found that maintaining good periodontal health is positively correlated with the prognosis of the disease in SARS-CoV-2 patients [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al investigated the causal relationship between periodontitis and SARS-CoV-2 infection based on MR (Mendelian Randomization) methods and concluded that there is a causal relationship between periodontitis and SARS-CoV-2 infection. [43] In their study, Meng et al found that periodontitis and GCF (Gingival crevicular uid) IL-1β (Interleukin-1β) levels, which are higher in periodontitis, are causally related to increased susceptibility to SARS-CoV-2 infection [21]. On the other hand, a study by Drozdzik et al showed that there was no causal connection between periodontitis and SARS-CoV-2 cases, but it was found that maintaining good periodontal health is positively correlated with the prognosis of the disease in SARS-CoV-2 patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that aspiration of saliva with a high viral load may carry the virus to the lower respiratory tract and increase the risk of developing more severe forms of the disease [42]. Numerous studies have investigated the potential presence of a relationship between periodontal diseases and SARS-CoV-2 infection [21,22,24]. Wang et al investigated the causal relationship between periodontitis and SARS-CoV-2 infection based on MR (Mendelian Randomization) methods and concluded that there is a causal relationship between periodontitis and SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned, several studies have considered the hypothesis of a possible association, even a causal role, between periodontitis and COVID-19 [112][113][114]. Their in-flammatory and infectious natures have been reported to be among the mechanisms linking both diseases [115,116].…”
Section: Implications For Health Policymentioning
confidence: 99%
“… 24 Given the urgency to investigate the potential causal link between periodontitis and coronary atherosclerosis. Scholars have employed MR analysis to study the relationship between periodontitis and multiple non-oral diseases, 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 including arthritis, hypertension, psoriasis, Parkinson's disease, inflammatory bowel disease (IBD), etc. However, most studies have not provided strong supporting a significant causal relationship between the periodontitis and these diseases, suggesting that periodontitis may be a comorbid condition or that other shared disease mechanisms are yet to be explored.…”
Section: Introductionmentioning
confidence: 99%